2022
DOI: 10.1172/jci160852
|View full text |Cite
|
Sign up to set email alerts
|

Purine nucleoside phosphorylase enables dual metabolic checkpoints that prevent T cell immunodeficiency and TLR7-associated autoimmunity

Abstract: Purine nucleoside phosphorylase (PNP) enables the breakdown and recycling of guanine nucleosides. PNP insufficiency in humans is paradoxically associated with both immunodeficiency and autoimmunity, but the mechanistic basis for these outcomes is incompletely understood. Here, we identify two immune lineage-dependent consequences of PNP inactivation dictated by distinct gene interactions. During T cell development, PNP inactivation is synthetically lethal with downregulation of the dNTP triphosphohydrolase SAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…These mononucleotides are further hydrolyzed by nucleosidases to nucleosides, which undergo phosphorolysis by nucleoside phosphorylase to yield nucleobases. PNP is an enzyme involved in purine metabolism, which can metabolize nucleosides into nucleobases . The results of the western blot showed that the content of PNP in gefitinib treatment group was significantly disordered (Figure S7D,E), which led to the disorder of nucleosides and nucleobases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These mononucleotides are further hydrolyzed by nucleosidases to nucleosides, which undergo phosphorolysis by nucleoside phosphorylase to yield nucleobases. PNP is an enzyme involved in purine metabolism, which can metabolize nucleosides into nucleobases . The results of the western blot showed that the content of PNP in gefitinib treatment group was significantly disordered (Figure S7D,E), which led to the disorder of nucleosides and nucleobases.…”
Section: Resultsmentioning
confidence: 99%
“…PNP is an enzyme involved in purine metabolism, which can metabolize nucleosides into nucleobases. 39 The results of the western blot showed that the content of PNP in gefitinib treatment group was significantly disordered (Figure S7D,E), which led to the disorder of nucleosides and nucleobases. In addition, nucleobases can be reused to synthesize nucleotides, which is only a remedial synthetic pathway for intracellular nucleotides.…”
mentioning
confidence: 99%
“…Inosine to R1P metabolism via PNP has clear importance in other biological contexts. PNP is established as an essential player in lymphocyte metabolism, and inosine can even completely substitute for glucose in fueling effector T cells in vitro 49,50 . On the clinical side, the PNP inhibitor forodesine is currently in a variety of clinical trials as a possible treatment for lymphomas (https://www.clinicaltrials.gov/ct2/ results?…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the JCI , a report by Abt and colleagues explored the consequences of deficiency of the enzyme purine nucleoside phosphorylase (PNP) ( 8 ). The authors used synthetic inhibitors of PNP to clarify the pathway through which PNP deficiency is toxic to developing T cells and also propose a mechanism for the association of PNP deficiency with autoimmunity through effects on TLR7.…”
Section: A Role For Tlr7 In Human Diseasementioning
confidence: 99%
“…Increased formation of germinal centers also occurred, even in the absence of immunization with exogenous antigen. In MRL-LPR mice, which are prone to developing autoimmunity, acceleration of lymphoproliferative and lupus-like autoimmunity was observed with five weeks of exposure to a PNP inhibitor ( 8 ). Further work is needed to more fully understand how the accumulation of purine nucleosides alters the consequences of TLR7 engagement, the full range of cell types in which these interactions occur, and which cytokines, other than IL-6, play roles in the acceleration of autoimmunity by PNP inhibitors.…”
Section: A Role For Tlr7 In Human Diseasementioning
confidence: 99%